Late presentation of congenital muscular torticollis in siblings - Sam Aruputha John, MS, MCh (ped surgery, India); Ahamed Faiz ali, MS, MRCS, FAMS (PEDSURG); Rasha kassem; Ali H. Ashkanani, MB, BCH, B.A.O (R.C.S.I); Ola Abdelfattah Taher, MSC (ped surgery); Hassan Ahmed Adly, MS (PEDSURG) (Elsevier, 2017)
Congenital muscular torticollis (CMT) is the third most common congenital musculoskeletal anomaly seen in children. It is a condition in which the affected sternocleidomastoid muscle becomes a fibrosed cord with associated shortening of the muscle. This leads to an ipsilateral side tilt of the neck and contralateral rotation of the face and chin to the other side. Apart from surgery various other treatment modalities are used to treat this condition. We present two siblings of Sudanese nationality with manifestation of Congenital Muscular Torticollis, a male child and female child at the age of 12 and 10 years respectively. Both had CMT of the right sternomastoid muscle. Both were delivered normally. They did not undergo any form of physiotherapy or surgical procedure since birth. Because of this neglected circumstances, the facial asymmetry and deformity were severe. Both the siblings were operated in our hospital with satisfactory result on follow up. Management for CMT starts during the early infancy and physiotherapy is the main treatment for this condition. But some of these CMT children may need surgical intervention to prevent further deterioration of cranial deformity and facial asymmetry. If these children are neglected and present later in life, they will have severe facial deformity with its associated sequelae. These patients are usually managed by other specialities worldwide. But awareness of these conditions is required among paediatric surgeons, as some of these children may be referred to them for treatment. In our case report we have also described various other modalities of treatment for this condition.